Remote controlled experiments for teaching over the Internet: A comparison of approaches developed in the PEARL project - Martyn Cooper (2002)
The PEARL project has been developing approaches for enabling real-world experiments to be conducted by students working, remotely from the laboratory, over the Internet. This paper describes these approaches and compares and contrasts three specific implementations of them both at the level of the nature of the practical work they support and the technical infrastructures that enables this to be conducted remotely. Initial evaluations by experts and representative student subjects are reported and key lessons for further development work by the project consortium, or others seeking to implement remote experiments, are outlined. Among the lessons learnt is that engineering realities associated with the equipment being used were difficult to accommodate in the generic architecture we initially envisaged. In fact the three implementations described adopted different architecture in their realisation of the PEARL approach. These are commented on in the paper together with notes on their implementation given available technologies.